Distance to isocenter is not associated with an increased risk for local failure in LINAC-based single-isocenter SRS or SRT for multiple brain metastases. (June 2021) - Kraft, Johannes; van Timmeren, Janita E.; Mayinger, Michael; Frei, Simon; Borsky, Kim; Stark, Luisa Sabrina; Krayenbuehl, Jerome; Zamburlini, Mariangela; Guckenberger, Matthias; Tanadini-Lang, Stephanie; Andratschke, Nicolaus
Highlights: Growing evidence for stereotactic radiotherapy in multiple brain metastases. Convenient and fast LINAC-treatment of multiple lesions with one isocenter (SIMT). Concerns of uncertainties on target coverage at extended distances to isocenter. Distance to isocenter does not impact local control with SIMT SRS/SRT. Abstract: Purpose: To evaluate the impact of the distance between treatment isocenter and brain metastases on local failure in patients treated with a frameless linear-accelerator-based single-isocenter volumetric modulated arc (VMAT) SRS/SRT for multiple brain metastases. Methods and materials: Patients treated with SRT for brain metastases (BM) between April 2014 and May 2019 were included in this retrospective study. BM treated with a single-isocenter multiple-target (SIMT) SRT were evaluated for local recurrence-free intervals in dependency to their distance to the treatment isocenter. A Cox-regression model was used to investigate different predictor variables for local failure. Results were compared to patients treated with a single-isocenter-single-target (SIST) approach. Results: In total 315 patients with a cumulative number of 1087 BM were analyzed in this study of which 140 patients and 708 BM were treated with SIMT SRS/SRT. Median follow-up after treatment was 13.9 months for SIMT approach and 11.9 months for SIST approach. One-year freedom from local recurrence was 87% and 94% in the SIST and SIMT group, respectively. Median distance to isocenter (DTI) was 4.7 cm (range 0.2–10.5) in the SIMT group. Local recurrence-free interval was not associated with the distance to the isocenter in univariable or multivariable Cox-regression analysis. Multivariable analysis revealed only volume as an independent significant predictor for local failure ( p -value <0.05). Conclusion: SRS/SRT using single-isocenter VMAT for multiple targets achieved high local metastases control rates irrespective of distance to the isocenter, supporting efficacy of single-isocenter stereotactic radiation therapy for multiple brain metastases.